The role of emotion in recognition with versus without cued-recall - Ryals, Anthony J. (Anthony Joseph), author; Cleary, Anne M., advisor; Malcolm, Matthew P. (Matthew Paul), committee member; Clegg, Benjamin A., committee member; McCabe, David P., committee member (Colorado State University. Libraries, 2010)
In the present study, we sought to examine the effects of emotion on the processes that subserve recognition memory. Specifically, we explored how two primary dimensions of emotion (negative valence and high arousal) separately impact the two processes of recognition memory (recollection and familiarity). To separately examine recollection and familiarity, the recognition without cued-recall method was used to separate out judgments of recognition that are accompanied vs. unaccompanied by cued-recall. Data from three experiments suggest that both negative valence and high arousal increase both cued-recall performance itself and recognition accompanied by cued recall, without affecting the ability to recognize in the absence of cued-recall. Additionally, two emotional biases were found. The first bias, found in a within-subjects manipulation, involves an increase in recognition ratings for cues corresponding to unrecalled negative items relative to cues corresponding to unrecalled neutral items. The second bias was an increase in recognition ratings for cues corresponding to negative and arousing nonstudied items that were identified relative to cues corresponding to neutral nonstudied items that were identified.
Department Head: Ernest L. Chavez.